(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Engineered cementitious composite (ECC) as one of the most promising types of strain-hardening cementitious composites (SHCC) has received worldwide attention. Polyvinyl alcohol (PVA) fibres have been proven as one of the more successful chopped reinforcement to achieve desired properties of ECC. Locally, this types of fibre is not available and still uneconomic choice to use. Research in this field, in Iraq, is still new although this composite has been under investigation in the last ten years in some countries such as the United States. This study points out the use of available discrete carbon fibre to reinforce cementitious matrix as an attempt to present ECC with locally available and economical components as composites with desirable strain-hardening performance that could help retrofitting and repairing existed deteriorating structures. Seven groups with volume fraction of carbon fibres ranging from 0% to 3% were considered to produce thin beams tested under bending conditions. The results showed an overwhelming performance of carbon fibres to add ductility to the cementitious composites with varied efficiency. Specimens with 2% volume fraction of fibres overcame the other groups when presented flexural strength 8 times more that of the control specimens and 8 mm mid-span deflection (vertical deflection), which represents notable ductility if compared with the control specimens that presents about 1mm. These results open up the opportunity to investigate and bring the research interests of future studies, locally, on this field.